PERENCANAAN PAJAK PADA PT STRAWLAND UNTUK TAHUN 2018 - Adrian Pranata, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research was conducted with the aim of making tax saving by conducting tax planning at the company of PT STRAWLAND. The object of this study is a financial report in the form of an income statement from PT STRAWLAND for the year ending in 2018.Based on research, then with the right tax planning, the company can reduce fiscal profit from Rp. 9,403,222,014 to Rp. 9,254,034,183 so that it will reduce the income tax payable by Rp. 3,108,080. Tax planning carried out is tax planning on PPh 21 by changing the calculation method into gross up method, final PPh tax planning by doing gross up on car rental costs, and tax planning for entertainment costs by making a nominative list so that the costs can be charged in calculating taxable profits.